2009
DOI: 10.1007/s10620-009-0893-2
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Dietary Fiber Protects Against Nonsteroidal Anti-inflammatory Drug-Induced Damage to the Small Intestine in Cats

Abstract: SDFs protect the small intestine against NSAID-induced damage, probably by compensating a barrier function of the mucin decreased by IND. Viscosities of the SDFs play a role, at least in part, in the protective effects of the SDFs on the small intestine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 26 publications
1
18
0
1
Order By: Relevance
“…We demonstrated that both the expression of COX isoforms and the levels of PGE 2 in the duodenum were increased after a meal and that the effect was suppressed by pretreatment with cimetidine, suggesting that the influx of gastric acid into the duodenum stimulates the local expression of COX isoforms and that the increase in COX isoforms contributes to the protection of mucosa through the enhanced PG synthesis during the postprandial period. We previously reported that the formation of IND-induced duodenal lesions in cats was markedly prevented by pretreatment with cimetidine or misoprostol (Satoh et al, 2009(Satoh et al, , 2010. This finding is consistent with the present results.…”
Section: Drugsupporting
confidence: 94%
“…We demonstrated that both the expression of COX isoforms and the levels of PGE 2 in the duodenum were increased after a meal and that the effect was suppressed by pretreatment with cimetidine, suggesting that the influx of gastric acid into the duodenum stimulates the local expression of COX isoforms and that the increase in COX isoforms contributes to the protection of mucosa through the enhanced PG synthesis during the postprandial period. We previously reported that the formation of IND-induced duodenal lesions in cats was markedly prevented by pretreatment with cimetidine or misoprostol (Satoh et al, 2009(Satoh et al, , 2010. This finding is consistent with the present results.…”
Section: Drugsupporting
confidence: 94%
“…Another recent study documented that soluble dietary fibers can protect cats from indomethacin-induced small intestinal lesions; dietary fibers act same as endogenous mucin [21]. Dietary fibers may also influence enterobacteria.…”
Section: Discussionmentioning
confidence: 99%
“…In order for a fiber to bind bile acids, it is required to be viscous in nature, and polydextrose is lower in viscosity for instance in comparison to pectin and guar gum which have high water binding capacity with higher viscosity and thus increased capability to bind bile acids [42,78]. Polydextrose has a high capacity to bind water, and it can for instance relieve constipation presumably due to this characteristic, but there is no gel formation by polydextrose in water and little viscosity [43,79,80].…”
Section: Role Of Polydextrose In Enterohepatic Bile Circulation and Imentioning
confidence: 99%